Design Of Eco-Creative Wood-Equipment Products For Product Design Learning Media In SMK Negeri 14 Bandung - Rachman, Chandra Wardana; Abas, Tati; Jubaedah, Yoyoh (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2018)
This research moved into the problem of not maximizing the utilization of the remaining pieces of wood practice Kriya Kayu students in SMKN 14 Bandung. This study aims to design a product of Eco-Creative based wood craft as a learning medium on product design subjects in SMK Negeri 14 Bandung. This research uses Research and Development (R D) method through Analysis, Design, Development, and Evaluation phase. The study sample consisted of two media instructional experts. The findings of the research results show the learning media materials from the utilization of waste wood pieces to produce learning media for Kindergarten in the form of pyramid numbers and the arrangement of geometric shapes are at very reasonable criteria. Media pyramid numbers and arrangement of geometric shapes that have been designed to show feasibility as a medium of learning from the aspect of identification, goals, visualization and function are at very reasonable criteria. Recommendations that can be submitted for product design subject teachers are expected to utilize and process waste wood pieces into a medium that can be used in the learning process. For later researchers to be developed into a medium used for the learning process of preschoolers or develop other types of learning media.